Iodine/TBHP-Promoted One-Pot Deoxygenation and Direct 2-Sulfonylation of Quinoline N-Oxides with Sodium Sulfinates: Facile and Regioselective Synthesis of 2-Sulfonylquinolines - Ladawan Sumunnee (2018)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim A highly efficient iodine/TBHP-mediated one-pot deoxygenative and regioselective 2-sulfonylation of quinoline N-oxides with sodium sulfinate salts has been developed. This metal-, base-, and phosphorus-free protocol employs readily accessible and easy-to-handle reagents and can be conveniently carried out at room temperature under mild conditions, providing an alternative access to a series of 2-sulfonylquinolines and other related heteroaryl sulfone products in moderate-to-excellent yields within a short reaction time.